2016
DOI: 10.1108/ilt-07-2015-0113
|View full text |Cite
|
Sign up to set email alerts
|

Conductive capacity and tribological properties of several carbon materials in conductive greases

Abstract: Purpose The purpose of this paper is to synthesize a new kind of conductive grease which possesses a prominent conductive capacity and good tribological properties. Design/methodology/approach A two-step method was used to prepare complex lithium-based grease. Ketjen black (KB), acetylene black (AB) and carbon black (CB) were characterized by transmission electron microscope and used as lubricant additives to prepare conductive greases. Conductive capacity was evaluated by a conductivity meter, a surface vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…Figure 4(a) depicts the SEM image of MG. MG exhibits a large two-dimensional planar structure, which is beneficial for promoting contact between the graphene sheets in grease to form a network, which improves the electrical and thermal conductivities of the grease. Moreover, this network functions as a protective film to minimize the friction and wear [20,25]. Figure 4(b) depicts the thermal stability of MG and MGLG.…”
Section: Analysis Of the Ag Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4(a) depicts the SEM image of MG. MG exhibits a large two-dimensional planar structure, which is beneficial for promoting contact between the graphene sheets in grease to form a network, which improves the electrical and thermal conductivities of the grease. Moreover, this network functions as a protective film to minimize the friction and wear [20,25]. Figure 4(b) depicts the thermal stability of MG and MGLG.…”
Section: Analysis Of the Ag Coatingmentioning
confidence: 99%
“…When the surface texture associates with the lubricant, the combination can exhibit some synergistic lubrication mechanisms including acting as micro-reservoirs of lubricants to increase the local lubricant supply and functioning as microhydrodynamic bearings to increase the load-carrying capacity, which can greatly enhance the tribological properties [8,[17][18][19]. However, the lubricant applied for sliding electrical contacts should possess outstanding lubricating ability and preferable conductivity [20][21][22]. When performing the functions of friction reduction, anti-wear, cooling, and corrosion prevention, the lubricants could also form conductive paths to transmit current between the contact interfaces, thereby reducing the ECR.…”
Section: Introductionmentioning
confidence: 99%
“…Various conductive additives can affect electrical properties. Ge et al [17] prepared conductive greases with carbon nanotubes, carbon black [18], ionic liquids [19][20][21][22][23], and Sb-doped SnO 2 [24]. They discovered that all these conductive additives improved the conductivity and tribological performances of conductive greases.…”
Section: Introductionmentioning
confidence: 99%
“…PTSCs showed excellent conductivity properties when the proportion of AlN/FG was 4/7 and 2/9. According to tunnel effect theory, with increasing of FG, the composite's conductive capacity improved because the distance between graphite sheets decreased, making it easier for electrons to cross the graphite layers . An interesting phenomenon was that the volume resistance of AlN/GF‐PTSC (2/9, containing ∼5% AlN and ∼25% FG) was higher than that of FG–PTSC (25% FG).…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the application requirement of thermal silicon composites used in power lines, electrical tribological properties are another important factor to be considered. Xia et al . have revealed that several additive materials, such as graphene, multiwalled carbon nanotubes, carbon black, and ionic liquids, enhance grease electrical and tribological properties, mainly because they form an effective conductive pathway for electrical transfer.…”
Section: Introductionmentioning
confidence: 99%